Pleistocene volcanism along the margins of the Canal de Ballenas transform fault, Gulf of California - Martín, Arturo; Schmitt, Axel Karl; Weber, Bodo; López-Martínez, Margarita (Revista mexicana de ciencias geológicas, 2022)
Pleistocene subaerial volcanism along the margins of the Ballenas Channel, northern Gulf of California, is represented by two morphologically young dacite dome complexes exposed at the opposite edges of sheared continental crust: Isla Coronado in coastal Baja California, and the Lobera volcanic complex in west-central Isla Ángel de la Guarda. Single crystal zircon U-Pb crystallization ages of Coronado and Lobera volcanoes range between ca. 250 and 1000 ka, indicating maximum ages for the eruptions. Eruption ages are directly constrained by an 40Ar/39Ar whole-rock age of 692 ± 164 ka for one of the lava units in the Lobera volcanic complex. Trace elements in Pleistocene zircon indicate continental affinity, which supports radiogenic (Nd, Sr) isotopic data that were modeled using different mixing and AFC scenarios indicating a MORB-type primary magma with significant (~10-20 %) crustal assimilation involving tonalitic basement of the eastern Peninsular Ranges Batholith.
Das PDF enthält zusätzlich ein Erratum von einer Seite
Gesehen am 11.05.2022